The Canonization of Ibn Mâjah: Authenticity vs. Utility in the Formation of the Sunni Ḥadîth Canon - Jonathan AC Brown (Revue des Mondes Musulmans et de la Méditerranée)
In Sunni Islam, the canonical ‘Six Books’ of hadith derive their authority as doctrinal references from scholarly consensus on their reliability as representations of the Prophet’s Sunna. One of the Six Boooks, the Sunan of Ibn Majah, however, presents a bizarre exception. Although it has been considered part of the Six Book collection since the late eleventh century, it has been consistently and severely criticized by Sunni scholars for the large number of unreliable hadiths it contains. Explaining the canonical status of Ibn Majah’s Sunan despite these criticisms requires recognizing that the hadith canon was based not only on authenticity but also on utility. The Six Books served to delimit the countless numbers of hadith in circulation into a manageable form, and Ibn Majah’s Sunan added to this canonical body a useful number of hadiths not found in the other Six Books. Sunni scholars themselves acknowledged that, in the case of Ibn Majah’s Sunan, utility trumped authenticity in the Sunni hadith canon.